ANALISIS PELATIHAN BUDIDAYA PINANG DAN STRATEGI PEMASARAN DALAM MENINGKATKAN PENDAPATAN KELOMPOK TANI MANDIRI - Ay Noor Rofik; Nuraini Asriati; Syamsuri Syamsuri (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2022)
AbstractThis research aims to review and analyze cultivation training and marketingstrategies in increasing the income of farmers gropus In Rasau Jaya. This form ofresearch is qualitative research with this type of case study research. The data sourcein this study is a member of a farming group consisting of 4 groups whose each groupcontains 5 members so that the total data source is 20 people. Its data collectiontechnique is to use data triangulation techniques consisting of observation, interviewand documentation. The results of this study showed that in the training of cultivationregarding material 1-3 given by the group of 1,2,3,4 already understand well allmaterials provided by the coaches, the masketing strategy carried out by 4 groupstends to use the same strategy that offers products in the form of fresh betel nut, dryand processed betel nut, the price offered Rp5,000-Rp60,000 distribution channelthrough the long process from farmers to export promotions carried out is a strategy.Public relations and personal selling. There is an increase in the income of the farmergroup 1-4 before and after the cultivation of betel nut; for the overall increase in theincome of the average farmer group is 5.41%Keywords: Training, Betel Cultivation, Marketing Strategy, Farmer’s Income